PENGARUH INFRASTRUKTUR JALAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA, 1976 â 2011 - , RYKI ABDULLAH, Dr. Akhmad Makhfatih, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper examine road infrastructure role on Indonesian economic growth period 1976 â 2011. Autoregressive Distributed Lag Error Correction Model (ARDL - ECM) is developed to analyze the long run effect and the short run effect between variables studied. The results demonstrate that road infrastructure does not have significant link to economic growth in the long run and short-run.